(untitled) (Observatorio Económico, 2015)
When rents have to be divided up, the players who are not at the negotiating table receive nothing. In the case of collusion, those seated at the table are suppliers and retailers; consumers are not invited to the table. The solution, however, comes from competition to win over the key guest so that the party can go on, but what if there is no competition? What happens if there is no need to woo the consumer with lower prices? Continue reading...